Working time reduction, mental health, and early retirement among part-time teachers at German upper secondary schools - a cross-sectional study - Seibt, Reingard; Kreuzfeld, Steffi (Frontiers in Public Health, 2023)
Objective Many secondary school teachers work part-time in order to cope with the high workload and to remain as healthy as possible until regular retirement. However, due to the acute shortage of teachers, the increase in the teaching obligation for part-time teachers (PTT) has become a topic of discussion in Germany. Whether a reduction in teaching hours is associated with benefits for mental health has not yet become evident. Therefore, this study investigated the relationship between the real working hours of PTT and their mental health as well as individual pension prognosis. Methods The cross-sectional study included 5,905 PTT at German upper secondary schools (female proportion: 81%, average age: 44 ± 9 years) who logged their working hours over four weeks. Four part-time groups (PTG) were formed based on the proportion of a full-time position worked: maximum (<100–90% = PTGmax – reference group – 17%), high (<90–75% = PTGhigh – 34%), medium (<75–50% = PTGmed – 40%) and low (<50% = PTGlow – 9%) teaching commitment. These groups were compared in terms of their average weekly working hours, mental health (inability to recover, risk of burnout) and predicted retirement age. Results The contractually agreed working time is exceeded to a relevant extent for PTT. The extent of unpaid overtime increases significantly the lower the teaching obligation is and lies on average between −0.4 (PTGmax) and 7.3 (PTGlow) hours/week. A reduction in teaching hours is neither related to the mental health of teachers nor to their decision to retire early (42%) or regularly (58%). However, predicted retirement is mainly explained by mental health status, gender and age (variance explanation: 24%, OR of predictors: maximum 2.1). One third of PTT reported inability to recover, 47% burnout symptoms and 3% a burnout syndrome. Conclusion Mental health is also a risk for PTT; reducing teaching hours alone does not improve it. However, good mental health increases the chance of regular retirement. Therefore, instead of a legal obligation, PTT should be encouraged to increase the number of teaching hours voluntarily in order to counteract the general shortage of teachers.